A study on the prevalence of Schistosoma Haematobium and Schistosoma Intercalatum in a rural community of Ogun State, Nigeria (South East Asia Journal of Public Health, 2015)
Urinary Schistosomiasis is endemic in Nigeria and continues to pose public health challenges especially in inhabitants of rural areas. This study was conducted in an attempt to determine the co-infection of Schistosoma haematobium and S. intercalatum in Apojola Community area of Abeokuta North LGA of Ogun State, Nigeria. Urine samples were analyzed in the Laboratory using sedimentation/centrifugation technique to determine schistosoma eggs. Positive urine samples were further confirmed using Ziehl-Neelsen (zn) staining method for differentiating S. haematobium from S. intercalatum eggs. The results indicate that 79 (52.7%) of the urine samples collected were positive for schistosoma eggs. Among the positive urine samples, 62% had S.haematobium while 38% had S. intercalatum eggs. Infections were found to be high in males 39 (55.7%) than female 40 (50%). Villagers who were